Culture and enculturation: Notes on the papal magisterium and the thougt of V´íctor And´rés Belaunde - Martínez Ferrer, Luis (Mercurio Peruano, 2016)
This article shows the importance of inculturation as a theological phenomenon according to the teaching of John Paul II, Benedict XVI and Francisco. It begins by considering the concept of culture confronted with some ideas of Víctor Andrés Belaunde and develops the concept and criteria of a proper inculturation. It points out some challenges of inculturation, as syncretism.